Groundwater Quality Assessment By Using Statistical Techniques and Water Quality Index- A Case Study - Raisul Islam, Kunwar. Raghvendra Singh (International Journal of Advanced Science and Technology, 2020)
Groundwater is an essential natural resources. It provides water for domestic as well as for irrigation purpose. It is essential to monitor the quality of groundwater at regular interval for proper resource management. In this study, groundwater quality of Chaumuhan (Mathura, India) has been assessed. Water samples were collected in post-monsoon season in the 2019 and analysed for nine physico-chemical parameters namely pH, Cl-, EC, Turbidity, alkalinity, F-, NH3 NO2- and NO3-.Th eexperimental results indicated that pH of water samples was either slightly acidic or slightly alkaline. Concentrations of Cl-, EC, TA, F-, NH3, NO2- and NO3are within the permissible limits of drinking water quality standards. However, Turbidity was exceeded the permissible limits in some sampling points during sampling period. The purpose of the study is to assess the suitability of the groundwater for drinking purposes using water quality index (WQI). The values of WQI indicate that water is suitable for drinking purposes after some basic treatment. Keywords: · Water quality index, Groundwater, Water quality.